A high‐throughput RNAi screen for detection of immune‐checkpoint molecules that mediate tumor resistance to cytotoxic T lymphocytes. Issue 4 (17th February 2015) - Khandelwal, Nisit; Breinig, Marco; Speck, Tobias; Michels, Tillmann; Kreutzer, Christiane; Sorrentino, Antonio; Sharma, Ashwini Kumar; Umansky, Ludmila; Conrad, Heinke; Poschke, Isabel; Offringa, Rienk; König, Rainer; et al.
Abstract The success of T cell‐based cancer immunotherapy is limited by tumor's resistance against killing by cytotoxic T lymphocytes (CTLs). Tumor‐immune resistance is mediated by cell surface ligands that engage immune‐inhibitory receptors on T cells. These ligands represent potent targets for therapeutic inhibition. So far, only few immune‐suppressive ligands have been identified. We here describe a rapid high‐throughput siRNA‐based screening approach that allows a comprehensive identification of ligands on human cancer cells that inhibit CTL‐mediated tumor cell killing. We exemplarily demonstrate that CCR9, which is expressed in many cancers, exerts strong immune‐regulatory effects on T cell responses in multiple tumors. Unlike PDL1, which inhibits TCR signaling, CCR9 regulates STAT signaling in T cells, resulting in reduced T‐helper‐1 cytokine secretion and reduced cytotoxic capacity. Moreover, inhibition of CCR9 expression on tumor cells facilitated immunotherapy of human tumors by tumor‐specific T cells in vivo. Taken together, this method allows a rapid and comprehensive determination of immune‐modulatory genes in human tumors which, as an entity, represent the 'immune modulatome' of cancer.